1983
DOI: 10.1111/j.1365-2818.1983.tb04166.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of methods for preparing easily damaged cuticular surfaces of plants for scanning electron microscopy

Abstract: SUMMARY Techniques were tested to ascertain the best method for preparing the surfaces of delicate plant cuticles for microscopic examination at magnifications not exceeding 10,000. Using scanning electron microscopy, comparative examinations were made of cuticles of fresh material, ambient dried, freeze dried, critical point dried, and frozen material kept at low temperature. Micrographs were compared with material examined using light microscopy which acted as a control at low magnification. Cuticles of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Previous studies (Eveling and McCall, 1983;Hardy et al, 1992;Sargent, 1983) have shown that the delicate bloom of epicuticular wax coatings on leaf surfaces can only be properly preserved by freezing specimens and examining them in the frozen state using a cryostage. Even freeze drying results in alteration of the wax structures due to distortion of the underlying cell wall and cuticle that supports them (Sargent, 1983).…”
Section: Plant Specimensmentioning
confidence: 99%
“…Previous studies (Eveling and McCall, 1983;Hardy et al, 1992;Sargent, 1983) have shown that the delicate bloom of epicuticular wax coatings on leaf surfaces can only be properly preserved by freezing specimens and examining them in the frozen state using a cryostage. Even freeze drying results in alteration of the wax structures due to distortion of the underlying cell wall and cuticle that supports them (Sargent, 1983).…”
Section: Plant Specimensmentioning
confidence: 99%
“…With low-temperature SEM (LTSEM) (Echlin, 1978;Marshall, 1987) cellular distortion can be avoided (Beckett & Read, 1986;Muller et al, 1986) and the fine structure of wax components is well preserved (Sargent, 1983;Pitcairn et al, 1986). Therefore, LTSEM has been successfully used for the investigation of plant surfaces (Parsons et al, 1974;Eveling & McCall, 1983;Read & Jeffree, 1991) and surfaces of fracture faces (Beckett & Porter, 1988;Guggenheim et al, 1991) as well as for measurements of stomatal opening (Wright, 1988;Van Gardingen et al, 1989).…”
mentioning
confidence: 99%
“…It is generally accepted that cryo-SEM images of hydrated biological specimens represent the most lifelike obtainable (Beckett & Read 1981;Eveling & McCall 1983;Read el al. 1983;Wilson & Robards 1984) despite some apparent inherent loss of resolution.…”
Section: Discussionmentioning
confidence: 99%